2020
DOI: 10.5430/ijhe.v10n1p157
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Civil Engineering in Higher Education: The Case of Mauritius

Abstract: Engineering plays a crucial role in everyday life and is the backbone of growth and development of the world including Mauritius. To embrace development, higher education institutions have to ensure that students are equipped with appropriate knowledge and skills to meet the needs of the country. Unfortunately, data shows that there is an underlying gender disparity in civil engineering training in higher education. It is imperative to understand the causes of gender inequity in engineering in higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The findings revealed that 'there is a gendered hierarchy within the micro community of the classroom in terms of the relationship among students themselves and between students and staff' (Baguant 2020). For example, women often find themselves excluded in class discussions when male students and male academic teaching staff are involved in the discussions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings revealed that 'there is a gendered hierarchy within the micro community of the classroom in terms of the relationship among students themselves and between students and staff' (Baguant 2020). For example, women often find themselves excluded in class discussions when male students and male academic teaching staff are involved in the discussions.…”
Section: Discussionmentioning
confidence: 99%
“…The experiences of participants revealed that the male students were often successful in the theory parts of the engineering curriculum (Baguant 2020). Female students seem to:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations